PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE IIP) -A CENSUS OF THE GENUS CROTALARIA - munk, w. j. de (Research Center for Biology, 1962)
A key is given to 38 species of which 29 are either native or introduced in Malaysia; 9 others have been reported from Malaysia, but no material was found to justify these records. They have been marked by an asterisk before their number.Crotalaria grandiflora Reinw. has been reduced to C. tetragona Andr.C. lejoloba Bartl. is probably the oldest name for C.ferruginea Grah. ex Bth., but as no type material could be located the latter name has been maintained for the time being.Some sheets of the Philippines identified as C. acicularis Buch.-Ham. ex Bth. have proved to belong to C.humifusa Grah. ex Bth. which is a new record for these islands.C. medicaginea Lamk. and C. trifoliasU-um Willd.have sometimes been merged; they are kept apart in this paper.A new record for Malaysia is the African C. cleomifolia Welw. which has been introduced in the Malay Peninsula as a green manure; whether it has spread as a weed is uncertain.Another newly recorded species in Malaya is C.undtiella Lamk. collected in 1954 for the first time locally in abundance along the sandy beach.C. prostrata Rottl.is newly recorded for the Philippines.Among the species a few are indifferent to climate, but most apparently prefer the occurrence of a dry season in various degree. In mapping the areas it has been found that they can easily be arranged in the drought classes distinguished in the first instalment.An index to synonyms and a list of collectors numbers have been added at the end.